Extension of Gap Bridgeability and Prevention of Oxide Lines in the Welding Seam through Application of Tools with Multi-Welding Pins - Marcel Hatzky; Stefan Böhm (Metals, 2021)
Friction stir welding has become important in many areas of production and is increasingly used for joining aluminum components. For long welding seams, conventional tools with only one welding pin reach their technical limitations due to low gap bridgeability. When welding aluminum, the stirred in surface layers, such as oxides, lead to a decrease in static and dynamic strength since linear accumulations are formed in the welding seam. The aim of the present study is to increase the gap bridgeability using tools with various welding pins and to prevent linear accumulation in the welding seam. The results show that a gap bridgeability of up to 2 mm for 4 mm material thickness is possible for the aluminum alloys EN AW 5083 H111 and EN AW 7020 T651. With the help of multi-pin tools, no impact of the gap width on the tensile strength was observed for joint gaps of up to 0.9 mm when using butt joint with a sheet thickness of 4 mm. Furthermore, the use of multi-pin tools showed significant influence on the prevention of linear accumulations in the welding seam. In addition, the oxide layers were finely distributed in welded joints using multi-pin tools.